2020
DOI: 10.3390/biom10040654
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Lectin from Tepary Bean (Phaseolus acutifolius) with Specific Recognition for Cancer-Associated Glycans: Production, Structural Characterization, and Target Identification

Abstract: Herein, we report the production of a recombinant Tepary bean lectin (rTBL-1), its three-dimensional (3D) structure, and its differential recognition for cancer-type glycoconjugates. rTBL-1 was expressed in Pichia pastoris, yielding 316 mg per liter of culture, and was purified by nickel affinity chromatography. Characterization of the protein showed that rTBL-1 is a stable 120 kDa homo-tetramer folded as a canonical leguminous lectin with two divalent cations (Ca2+ and Mn2+) attached to each subunit, confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Later on, a polyclonal antibody against TBLF was developed. Recently, as it was necessary to produce a recombinant lectin from Tepary bean (rTBL-1) by using Pichia pastoris yeast [ 9 ], we developed a specific polyclonal antibody against the recombinant lectin for its detection in specific tissues, serum, and fluids throughout the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Later on, a polyclonal antibody against TBLF was developed. Recently, as it was necessary to produce a recombinant lectin from Tepary bean (rTBL-1) by using Pichia pastoris yeast [ 9 ], we developed a specific polyclonal antibody against the recombinant lectin for its detection in specific tissues, serum, and fluids throughout the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…The rTBL-1 was subjected to an additional in silico digestion, but none of the generated peptides were big enough to conduct an interaction (peptide mass < 500 Da, data not shown). Previous studies using glycan arrays and isothermal titration calorimetry showed that rTBL-1 recognized 14 β1-6 branched N-glycans independently of their size, where β-D-galactose, β-D-N-acetyl-glucosamine, β-D-mannose, α-L-fucose, and sialic acid were found to be part of the recognized glycans [ 9 ]. Sialic acid and N-acetyl-glucosamine exhibited the highest binding affinity, as indicated by the lowest binding energies, suggesting that the rTBL-1 could directly interact with membrane components and its possible internalization as shown by Western blot, immunohistochemistry, and mass spectrometry analyses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations